2013
DOI: 10.1016/j.bbamcr.2013.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Association of luteinizing hormone receptor (LHR) mRNA with its binding protein leads to decapping and degradation of the mRNA in the p bodies

Abstract: Luteinizing hormone receptor (LHR) undergoes downregulation during preovulatory LH surge through a post-transcriptional mechanism involving an RNA binding protein designated as LRBP. The present study examined the mechanism by which LRBP induces the degradation of LHR mRNA, specifically the role of decapping of LHR mRNA and the translocation of LRBP-bound LHR mRNA to degradative machinery. Immunoprecipitation of the complex with the 5’cap structure antibody followed by real time PCR analysis showed progressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The active SREBP translocates to the nucleus and activates transcription of target genes, including LRBP, by binding to sterol response elements (SREs) in the promoter/enhancer regions of multiple target genes. LRBP then binds LHCGR mRNA and targets it for degradation [12]. Based on the present results combined with those of previous studies, a schematic model that depicts the molecular mechanism illustrating the role of miR-122 in FSH-induced LHCGR mRNA expression is presented in Fig 6.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The active SREBP translocates to the nucleus and activates transcription of target genes, including LRBP, by binding to sterol response elements (SREs) in the promoter/enhancer regions of multiple target genes. LRBP then binds LHCGR mRNA and targets it for degradation [12]. Based on the present results combined with those of previous studies, a schematic model that depicts the molecular mechanism illustrating the role of miR-122 in FSH-induced LHCGR mRNA expression is presented in Fig 6.…”
Section: Discussionsupporting
confidence: 55%
“…Biochemical characterization of LRBP established its identity as being mevalonate kinase (MVK) [8, 9]. LHCGR mRNA and LRBP expression show a reciprocal relationship at different stages of the ovarian cycle since at elevated levels of LHCGR expression, LRBP expression showed a decrease, whereas higher levels of LRBP were seen in response to the preovulatory LH surge, when LHCGR expression is transiently suppressed [12]. Further studies demonstrated that LRBP (MVK), a member of the oxysterol-responsive gene family, is regulated by miR-122, a microRNA that is expressed in the liver as well as in rodent and human ovaries [10, 11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Degradation of the LHR mRNA is the main process responsible for this rapid decrease in expression (Lu et al 1993). The mechanism of LHR transcript decay is not fully understood, but at least one protein, LHR mRNA binding protein (LRBP), binds to this transcript and accelerates its degradation (Hoffman et al 1991;Menon et al 2013).…”
Section: Introductionmentioning
confidence: 99%